2020
DOI: 10.5603/gp.2020.0104
|View full text |Cite
|
Sign up to set email alerts
|

Polish Society of Gynecologists and Obstetricians recommendation on the use of antiseptics for treatment of inflammatory vaginitis

Abstract: Undertook the analysis of literature, specialist knowledge and clinical experience on treatment options for non-specific vaginal inflammations of bacterial, fungal, mixed and unknown aetiology. The recommendation presents the current state of knowledge on this subject on the day of the published analysis. However, the expert group reserves the right to update this position in the event of new and significant scientific reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In gynecology, the use of PHMB in the treatment of inflammatory and dysbiotic diseases of the vagina has been determined since it does not have an inhibitory effect on the growth of Lactobacillus spp. and does not have strong toxicity or allergenicity when used vaginally [ 54 , 55 ]. Polyhexanide is mentioned in the literature for the treatment of acanthamoebic keratitis [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In gynecology, the use of PHMB in the treatment of inflammatory and dysbiotic diseases of the vagina has been determined since it does not have an inhibitory effect on the growth of Lactobacillus spp. and does not have strong toxicity or allergenicity when used vaginally [ 54 , 55 ]. Polyhexanide is mentioned in the literature for the treatment of acanthamoebic keratitis [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dequalinium chloride is recommended by several international and European guidelines as alternative treatment for BV or inflammatory vaginitis. 8,10,11,[31][32][33] Dequalinium chloride adsorbs into the cell surface, altering its permeability; disrupts protein synthesis; and induces protein denaturation and precipitation of nucleic acids. 25 Due to these multiple modes of action, the development of resistance is unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have reported the efficacy and safety of dequalinium chloride against vaginal infections. Dequalinium chloride is recommended by several international and European guidelines as alternative treatment for BV or inflammatory vaginitis . Dequalinium chloride adsorbs into the cell surface, altering its permeability; disrupts protein synthesis; and induces protein denaturation and precipitation of nucleic acids .…”
Section: Introductionmentioning
confidence: 99%